Synthesis, Characterization and Antimicrobial activity of Azo-azomethine Metal Complexes - Haitham kadhim Dakheel (Al-Qadisiyah Journal of Pure Science, 2023)
In the research, modern complexes also ligand (L) had been synthesized then characterized by using molar conductance measurements, (C.H.N.S), mass spectrum, magnetic susceptivity, “H1-NMR, (FT-IR)” Spectroscopy , (TGA), “UV-Visb.” Spectroscopy ,’X-ray studies” and scanning electron microscope (SEM). mole ratio [M:L] were [1:1] for Silver(I) also gold(III) ions but [1:2] to Copper(II) ion . The data optained from the various measurement indicater the Cu(II) and Ag(I) complexes have octahedral and tetrahedral geometry on respectively while square planar geometry for the Au(III) complex. We note that the copper complex [Cu(L)2Cl2] .H2O prepared has a high activity and sensitivity to the direction of the vital efficacy of coli Escherichia bacteria, but all prepared compounds have no activity against aureus Staphylococcus bacteria. As for alternaria fungi, we note that the silver complex of the prepared has a high effect and sensitivity to the direction of the vital efficacy of Alternaria fungi. The results will be clearly defined as shown in table 6 and shape (14)